Laurence anyways [videorecording (DVD)] - Dolan, Xavier; Poupaud, Melvil; Clément, Suzanne; Baye, Nathalie, 1948-; Chokri, Monia (Breaking Glass Pictures, 2013)
In the '90s, Laurence tells his girlfriend Fred that he wants to become a woman. In spite of the odds, they confront the prejudices of their friends, ignore the counsel of their families, and brave the phobias of the society they offend. For ten years, they try to live through this transition, and embark on an epic journey which, unbeknownst to them, may cost Fred and Laurence their love.